Clinical Safety Profile of Corneal Collagen Cross-Linking: A Longitudinal Analysis of Endothelial Integrity and Morphological Stability - Ashash, Sabah Lafta; Mohammed, Hussein Abdulhadi; Hamied, Furkaan Majied (Archives of Clinical and Biomedical Research, 2026)
Background: Keratoconus is a non-inflammatory conical ectasia of cornea that often exhibits bilateral asymmetric progression over time. Objective: To assess the effectiveness of corneal collagen cross-linking (CXL) on endothelial cell density, endothelial morphology, central corneal thickness, and corneal volume in cases with keratoconus. Methods: This prospective interventional research involved forty eyes from 22 patients with Stage I and II keratoconus. All patients underwent standard epithelium-off CXL (Dresden protocol). Preoperative and threemonth postoperative assessments included non-contact specular microscopy to measure endothelial cell density (ECD), coefficient of variation (CV), hexagonality percentage (HEX%), and central corneal thickness (CCT). Keratometric parameters and corneal volume were also evaluated. Results: The average preoperative and postoperative values of cell density were 2899.75 ± 299 cells/mm² and 2812.55 ± 218 cells/mm², respectively. Endothelial cell density showed a statistically significant decrease in three months postoperatively (P = 0.001). Coefficient of variation significantly increased (P = 0.001), while hexagonality significantly reduced (P-value equal to 0.001). No substantial difference has been identified in central corneal thickness. Significant reductions were detected in K1, K2, Kmax, and corneal volume. Keratoconus stage showed significant correlations with CCT change, CV change, and HEX change, but not with ECD change. Corneal volume change is related positively with ECD change (P= 0.021) and negatively with HEX change (P= 0.031). Conclusion: Standard CXL effectively stabilizes early keratoconus, reducing keratometry and volume. Despite minor morphological shifts, endothelial density and corneal thickness remained stable, confirming the procedure's relative safety while necessitating diligent postoperative monitoring for patient safety.